1992
DOI: 10.1159/000310316
|View full text |Cite
|
Sign up to set email alerts
|

Exudative Retinal Detachment Subsequent to Retinal Vein Occlusion

Abstract: Previous studies have shown the possible development of exudative retinal detachment (ERD) as a complication of retinal vein occlusion (RVO). Considering 473 consecutive cases of RVO, only 3 cases of ERD with peculiar clinical aspects were discovered. In the first case the ERD followed a branch RVO but it developed in the opposite quadrant, with a late occurrence of venous retinal collaterals. In the second case, the ERD developed after a central RVO, having a retinoschisis aspect, with the subsequent occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…SRD-type DME may appear very early in the evolution of DME 22 or may precede cystoid changes, 23 and the pathogenesis of serous retinal fluid in diabetes could result from hyperpermeability 23 or RPE dysfunction. 24,25 Diabetic choroidopathy may directly induce choroidal ischemia, leading to RPE dysfunction, or it may indirectly impair the ability of RPE to pump fluid due to factors affecting vascular permeability. Thus, it is speculated that the SRD-type DME is the result of increased ChT, which implies diabetic ischemic choroidopathy.…”
Section: Discussionmentioning
confidence: 99%
“…SRD-type DME may appear very early in the evolution of DME 22 or may precede cystoid changes, 23 and the pathogenesis of serous retinal fluid in diabetes could result from hyperpermeability 23 or RPE dysfunction. 24,25 Diabetic choroidopathy may directly induce choroidal ischemia, leading to RPE dysfunction, or it may indirectly impair the ability of RPE to pump fluid due to factors affecting vascular permeability. Thus, it is speculated that the SRD-type DME is the result of increased ChT, which implies diabetic ischemic choroidopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to more recent studies [28,29,30,31], this prevalence is much higher than previously reported. Previous studies [32,33,34,35] investigated the possible development of SRD as a complication of BRVO by ophthalmoscopic examination and found it to be a very rare event, occurring in case of severe vein occlusion with marked macular nonperfusion. In contrast, in our series, SRD was found both in eyes with ischemic and perfused ME.…”
Section: Discussionmentioning
confidence: 99%
“…Typical retinal findings include tortuousity and dilation of the retinal vein, retinal haemorrhage and serous detachment (Ravalico & Battaglia Parrodi 1992). Macular oedema is a common cause of visual impairment in patients with BRVO (Wallow et al 1988).…”
Section: Introductionmentioning
confidence: 99%